Pengaruh Price to Book Value (PBV), Earning Per Share (EPS) dan Price Earning Ratio (PER) Terhadap Harga Saham Pada Perusahaan Pertambangan yang Terdaftar pada Bursa Efek Indonesia (BEI) Periode Tahun 2021 - 2023 - Kasyaful Asror; RA Sista Paramita (Jurnal Ilmu Manajemen, 2026)
The mining sector plays a strategic role in Indonesia's economy and has become one of the most attractive investment sectors due to its significant contribution to national economic growth and export performance. As a result, stock price movements in mining companies are closely associated with investors' evaluations of corporate financial performance. This study aims to examine the effects of Price to Book Value (PBV), Earnings Per Share (EPS), and Price Earnings Ratio (PER) on the stock prices of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. A quantitative research approach was employed using secondary data obtained from the IDX. The sample consisted of 62 mining companies selected through purposive sampling, resulting in 186 firm-year observations. Data were analyzed using multiple linear regression with SPSS version 25 after satisfying the classical assumption tests. The findings reveal that PBV and EPS have a positive and statistically significant effect on stock prices, whereas PER does not significantly influence stock prices. These results indicate that investors in the mining sector place greater emphasis on valuation and profitability indicators than on market expectation measures when making investment decisions. This study contributes to the literature on stock valuation in the mining industry and provides practical implications for investors, corporate managers, and policymakers in assessing investment opportunities and improving financial decision-making.